The effect of flaw on rock mechanical properties under the Brazilian test - Yu Zhou; Guang Zhang; Shunchuan Wu; Li Zhang (Kuwait Journal of Science)
Tensile strength is one of the most significant parameters for rock. Rock-like materials were used to prefabricate Brazilian disc specimens containing a single flaw. Meanwhile, based on particle flow theory and the particle flow code 2 dimension (PFC2D) program, the effects of flaw length and dip angle on the specimens’ mechanical properties under Brazilian test were investigated, and a formula for tensile strength of specimens containing a single flaw under the Brazilian test was constructed. The results are shown as follows. When the flaw length is consistent, the tensile strength of specimens decreases initially and then increases with an increase in the flaw dip angle. When the flaw dip angle is consistent, the tensile strength of specimens decreases gradually with an increase in the flaw length. With an increase in the flaw length, the effect of flaw on the failure mode of specimens becomes more pronounced, and the amount of acoustic emission decreases and the distribution range of fracture magnitude shrinks.